2015
DOI: 10.1080/10916466.2014.954670
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of Crude Oil Contaminated Soil

Abstract: A laboratory study was undertaken to bioremediation crude oil contaminated soil by isolated strains. Pseudomonas strain A as the most superior indigenous biodegrader was selected. At the optimal growth condition of pH 7 and with 5 g/L NaCl, cosubstrate α-lactose, and inorganic salt FeSO 4 , 82.3% of crude oil degradation efficiency was obtained. Furthermore, characteristics of chemical composition during the biotreatment indicated that saturation hydrocarbons and some aromatics were effectively removed by stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Although biosurfactant solutions have a considerable capacity to extract crude oil from polluted soil by washing conditions, the results showed that the washing-temperature efficiency of crude oil removal from contaminated soil was the most significant factor, compared with the least influential factor which was washing time [2]. In turn, the bioremediation of crude oil polluted soil was achieved by isolating strains of the most efficient biodegradable material in the laboratory; this study demonstrates that many aromatic and saturation hydrocarbons with a chemical composition that is similar to that of crude oil were extracted successfully by the strain [19]. With different remediation approaches, the active degradation of crude oil contaminated saline soil can be achieved by using nitrogen additions, the inoculation of arbuscular mycorrhizas, and the cultivation of Suaeda salsa [20].…”
Section: Introductionmentioning
confidence: 79%
“…Although biosurfactant solutions have a considerable capacity to extract crude oil from polluted soil by washing conditions, the results showed that the washing-temperature efficiency of crude oil removal from contaminated soil was the most significant factor, compared with the least influential factor which was washing time [2]. In turn, the bioremediation of crude oil polluted soil was achieved by isolating strains of the most efficient biodegradable material in the laboratory; this study demonstrates that many aromatic and saturation hydrocarbons with a chemical composition that is similar to that of crude oil were extracted successfully by the strain [19]. With different remediation approaches, the active degradation of crude oil contaminated saline soil can be achieved by using nitrogen additions, the inoculation of arbuscular mycorrhizas, and the cultivation of Suaeda salsa [20].…”
Section: Introductionmentioning
confidence: 79%
“…The study of Sasaki et al [140] revealed that degradation halts at a pH value of 2, but composting may attain degradation efficiency up to 83% at pH 7. More so, the study by Yan et al [23] on the effect of changes in pH on hydrocarbon degradation rates revealed that the lowest degradation was at pH 3 (4%) and the degradation rate was optimal at pH 7 (72%). As the pH value rise to 9, Nitrogen was no longer available to microbes as nutrient due to the formation of ammonia gas confirmed by the urine-like smell that oozes out into the environment [142].…”
Section: Ph Valuementioning
confidence: 99%
“…To improve composting process operation and result [21], its operating parameters affecting compost time, stability and maturity need to be enhanced [22]. In other words, successful optimization of composting parameters such as operating temperatures, microbial inoculum concentration, turning frequencies, transformation time, percentage moisture content and Carbon-Nitrogen (C/N) ratio would shorten the composting time and increase products quality [23,24,25,26,8].…”
Section: Introductionmentioning
confidence: 99%
“…Aliphatic hydrocarbons are partially oxidized by many microbes, but can be fully metabolized by only a few species (Pseudomonas, Nocardia, Xanthomonas, Bacterium, Corynebacterium, Mycobacterium, Acinetobacter) [72,74]. Biodegradation of aromatic hydrocarbons depends on their number of benzene rings and their structural complexity [75].…”
Section: Phytoremediation Of Oil-polluted Soilsmentioning
confidence: 99%